Method for preparing Co3O4 nano spinel coating on surface of SUS430 stainless steel

Co3O4 nano-spinel coating is prepared on the surface of SUS430 stainless steel through ALD technology, which solves the problem of limited performance of stainless steel in high-temperature environments, realizes the density and adhesion of the coating, and improves the high-temperature oxidation resistance, conductivity and Cr resistance.

CN119506832APending Publication Date: 2025-02-25TAIYUAN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411580430.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The performance of SUS430 stainless steel is limited in high temperature environments, mainly due to the thickness and deterioration of the Cr2O3 layer, which leads to a decrease in conductivity and accelerated oxidation. The existing coating technology has shortcomings in uniformity, thickness control and bonding strength.

Method used

Atomic layer deposition (ALD) technology was used to prepare Co3O4 nanospinel coating on the surface of SUS430 stainless steel. Cobalt dicetum was used as a precursor and ozone was used as an oxidizing agent to perform high-purity nitrogen purge to ensure the density and adhesion of the coating.

Benefits of technology

The prepared Co3O4 nano spinel coating is dense and uniform, has strong adhesion, and has excellent high-temperature oxidation resistance, conductivity and Cr resistance. It effectively blocks oxidation medium, slows down the thickness of the Cr2O3 film, and maintains the conductive properties of stainless steel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506832A_ABST
    Figure CN119506832A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a Co3O4 nano spinel coating on the surface of SUS430 stainless steel, belongs to the technical field of preparation of inert nano coatings, solves the technical problem of surface modification of the SUS430 stainless steel, and comprises the following steps: S1, pretreatment of a base material; s2, constructing hydroxyl active sites on the surface of the base material, depositing a cobaltocene atomic layer on an atomic layer on the surface of the base material, purging with high-purity nitrogen to remove an unreacted precursor and by-products after precursor pulse, and fully reacting an oxidizing agent with the cobaltocene atomic layer deposited on the surface of the base material to obtain a cobaltocene precursor; the unreacted oxidizing agent and by-products after oxidizing agent pulse are purged and removed through high-purity nitrogen, and a nanometer Co3O4 coating is deposited on an ALD atomic layer on the surface of the SUS430 stainless steel base material; and S3, sintering treatment. The Co3O4 nano spinel coating prepared on the surface of the base material is compact and uniform, has strong adhesive force, and also has excellent high-temperature oxidation resistance, conductivity and Cr resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of inert nano coating preparation, and specifically relates to a method for preparing Co3O4 nano spinel coating on the surface of SUS430 stainless steel. Background Art

[0002] SUS430 stainless steel is widely used in engineering fields due to its excellent corrosion resistance and mechanical strength. However, its performance is often limited in high temperature environments. The main reason is the thickening and degradation of the Cr2O3 layer. The thickening of the Cr2O3 layer will lead to a decrease in conductivity, and the degradation of the Cr2O3 layer will expose the underlying metal, forming defects such as cracks, voids and particle peeling, accelerating the oxidation process and increasing the risk of pitting. Therefore, it is particularly important to improve the high temperature performance of SUS430 stainless steel through surface modification technology, which can not only extend its service life, but also expand its application in harsh environments.

[0003] Among the many methods to improve the performance of SUS430 stainless steel, the preparation of protective coatings is recognized as an effective strategy. Traditional coating technologies, including physical vapor deposition (PVD), chemical vapor deposition (CVD) and electrochemical deposition, each have their own advantages, but they still have limitations in coating uniformity, thickness control and bonding strength with the substrate material. In contrast, atomic layer deposition (ALD), as a high-precision self-limiting thin film deposition technology, can deposit materials layer by layer in a single atomic layer manner, ensuring the uniformity and density of the coating as well as controllable thickness, which lays a solid foundation for improving the film-substrate bonding performance.

[0004] At present, ALD technology has been applied to the preparation of oxides such as TiO2, Al2O3, and Ta2O5 on the surface of stainless steel, but research on Co3O4 thin films on the surface of stainless steel has not been reported. Co3O4 is a transition metal oxide with a spinel structure, which exhibits mixed valence, excellent thermal stability, and good electrical conductivity. Under high temperature conditions, the Co3O4 spinel coating can effectively block the oxidizing medium, slow down the further thickening of the Cr2O3 layer, and maintain the conductivity of stainless steel. In addition, its excellent conductivity can also improve the charge transfer characteristics of the stainless steel surface, further improving its performance in high-temperature oxidizing environments. Summary of the invention

[0005] The main purpose of the present invention is to overcome the deficiencies in the prior art and solve the technical problem of surface modification of SUS430 stainless steel. The present invention provides a method for preparing a Co3O4 nano-spinel coating on the surface of SUS430 stainless steel. The Co3O4 nano-spinel coating prepared on the surface of the substrate is dense and uniform, has strong adhesion, and has excellent high-temperature oxidation resistance, electrical conductivity and Cr resistance.

[0006] The present invention is implemented by the following technical scheme: A method for preparing a Co3O4 nano-spinel coating on the surface of SUS430 stainless steel comprises the following steps: S1. Substrate pretreatment: S1-1, using a wire cutting machine to cut the SUS430 stainless steel plate into substrates with a size of 15 mm in length × 15 mm in width × 1 mm in thickness; S1-2, using 120 mesh, 240 mesh, 400 mesh, 600 mesh, 800 mesh and 1000 mesh sandpaper in sequence to grind and polish the surface of the substrate prepared in step S1-1; S1-3, placing the substrate after grinding and polishing in step S1-2 into water and anhydrous ethanol in turn, performing ultrasonic cleaning for 15 to 20 minutes respectively, blowing dry after cleaning, immersing in anhydrous ethanol, sealing and storing for later use; S2, SUS430 stainless steel substrate surface ALD atomic layer deposition nano Co3O4 coating: S2-1, taking out the substrate sealed and stored in anhydrous ethanol in step S1, blowing it dry and placing it in the reaction chamber of the ALD equipment, introducing ozone into the reaction chamber with a pulse time of 30 seconds, and constructing hydroxyl active sites on the surface of the substrate; S2-2, using cobaltocene as a precursor, first, heating the cobaltocene to 80°C (to obtain the vapor pressure required for the reaction) and then introducing it into the reaction chamber of the ALD equipment; then, setting the deposition temperature of the ALD equipment to 220°C, the precursor pulse time to 5.5 seconds, and the number of cycles to 2000 cycles; finally, standing for 16 seconds after the precursor pulse, so that the cobaltocene in the reaction chamber can fully complete chemical adsorption at the active site, and the atomic layer containing the cobalt element is deposited on the substrate surface by ALD atomic layer deposition; S2-3, using high-purity nitrogen as carrier gas, using high-purity nitrogen to purge, to remove unreacted precursors and by-products after the precursor pulse, the flow rate of high-purity nitrogen is 50 sccm, and the purge time is 30 seconds; S2-4. First, ozone is used as an oxidant and introduced into the reaction chamber of the ALD equipment with a flow rate of 20 sccm; then, the deposition temperature of the ALD equipment is maintained at 220° C. and the pulse time of the oxidant is 0.1 second; finally, the oxidant is allowed to stand for 25 seconds after the pulse to allow the oxidant to fully react with the cobaltocene atomic layer deposited on the surface of the substrate; S2-5, using high-purity nitrogen to purge again to remove unreacted oxidant and by-products after the oxidant pulse, the flow rate of high-purity nitrogen is 50 sccm, and the purge time is 30 seconds; S2-6, after the temperature of the reaction chamber drops to room temperature, take it out and deposit a nano-Co3O4 coating on the surface of the SUS430 stainless steel substrate by ALD atomic layer deposition; S3. Sintering the SUS430 stainless steel substrate with the surface ALD atomic layer deposition nano-Co3O4 coating obtained in step S2: first, heating to 600°C at a heating rate of 5°C / min in an air atmosphere, and keeping the temperature for 3 hours; then, continuing to heat to 800°C at a heating rate of 5°C / min, and keeping the temperature for 2 hours; finally, cooling to room temperature with the furnace to obtain a Co3O4 spinel structure, thereby completing the preparation of the Co3O4 nano-spinel coating (ALD-Co3O4 nano-spinel coating) on ​​the surface of the SUS430 stainless steel substrate.

[0007] Furthermore, in the step S2-6, the thickness of the nano-Co3O4 coating deposited by ALD atomic layer deposition on the surface of the SUS430 stainless steel substrate is 100 nm.

[0008] The beneficial effects of the present invention are: 1. Co3O4 is a transition metal oxide with a spinel structure, which has mixed valence, excellent thermal stability and good electrical conductivity. The present invention successfully prepared a uniform, dense and highly adhesive Co3O4 spinel film on the surface of SUS430 stainless steel using ALD technology, filling this technical gap; 2. The present invention makes up for the shortcomings of the coating uniformity, thickness control and bonding strength with the base material after surface modification of the SUS430 stainless steel substrate. The prepared Co3O4 nano-spinel coating is dense and uniform with strong adhesion. At the same time, due to the inherent advantages of ALD technology, the thickness and composition of the nano-coating can be accurately controlled, and it has the characteristics of film formation on surfaces with complex shapes; 3. The present invention improves the problems of over-oxidation, decreased conductivity and Cr overflow of SUS430 stainless steel under high temperature conditions. The prepared Co3O4 nano-spinel coating can effectively block the oxidizing medium, slow down the thickening of the Cr2O3 film, maintain the conductive properties of the stainless steel, and has excellent high-temperature oxidation resistance, conductivity and Cr resistance. It provides a new technical path for stainless steel surface modification and has important scientific research and industrial application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 This is a comparison of the SEM microscopic morphology of the ALD-Co3O4 nano-spinel coating and its oxidation; the oxidation time is 0h, 50h, 100h and 200h respectively; Figure 2 This is the XRD phase analysis diagram of ALD-Co3O4 nano-spinel coating and its oxidation; Figure 3 The XPS Co 2p spectra of ALD-Co3O4 nanospinel coating and its thermal conversion; Figure 4This is a comparison chart of the oxidation kinetics curves of the ALD-Co3O4 nano-spinel coating and the SUS430 substrate; Figure 5 This is a comparison chart of the surface specific resistance (ASR) of the ALD-Co3O4 nano-spinel coating and the SUS430 substrate; Figure 6 This is a comparison chart of the relative content of Cr 2p elements on the surface of ALD-Co3O4 nano-spinel coating and SUS430 substrate. DETAILED DESCRIPTION

[0010] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.

[0011] A method for preparing a Co3O4 nano-spinel coating on a SUS430 stainless steel surface comprises the following steps: S1. Substrate pretreatment: S1-1, using a wire cutting machine to cut the SUS430 stainless steel plate into substrates with a size of 15 mm in length × 15 mm in width × 1 mm in thickness; S1-2, using 120 mesh, 240 mesh, 400 mesh, 600 mesh, 800 mesh and 1000 mesh sandpaper in sequence to grind and polish the surface of the substrate prepared in step S1-1; S1-3, placing the substrate after grinding and polishing in step S1-2 into water and anhydrous ethanol in turn, performing ultrasonic cleaning for 15 to 20 minutes respectively, blowing dry after cleaning, immersing in anhydrous ethanol, sealing and storing for later use; S2, SUS430 stainless steel substrate surface ALD atomic layer deposition nano Co3O4 coating: S2-1, taking out the substrate sealed and stored in anhydrous ethanol in step S1, blowing it dry and placing it in the reaction chamber of the ALD equipment, introducing ozone into the reaction chamber with a pulse time of 30 seconds, and constructing hydroxyl active sites on the surface of the substrate; S2-2, using cobaltocene as a precursor, first, heating the cobaltocene to 80°C (to obtain the vapor pressure required for the reaction) and then introducing it into the reaction chamber of the ALD equipment; then, setting the deposition temperature of the ALD equipment to 220°C, the precursor pulse time to 5.5 seconds, and the number of cycles to 2000 cycles; finally, standing for 16 seconds after the precursor pulse, so that the cobaltocene in the reaction chamber can fully complete chemical adsorption at the active site, and the atomic layer containing the cobalt element is deposited on the substrate surface by ALD atomic layer deposition; S2-3, using high-purity nitrogen as carrier gas, using high-purity nitrogen to purge, to remove unreacted precursors and by-products after the precursor pulse, the flow rate of high-purity nitrogen is 50 sccm, and the purge time is 30 seconds; S2-4. First, ozone is used as an oxidant and introduced into the reaction chamber of the ALD equipment with a flow rate of 20 sccm; then, the deposition temperature of the ALD equipment is maintained at 220° C. and the pulse time of the oxidant is 0.1 second; finally, the oxidant is allowed to stand for 25 seconds after the pulse to allow the oxidant to fully react with the cobaltocene atomic layer deposited on the surface of the substrate; S2-5, using high-purity nitrogen to purge again to remove unreacted oxidant and by-products after the oxidant pulse, the flow rate of high-purity nitrogen is 50 sccm, and the purge time is 30 seconds; S2-6, after the temperature of the reaction chamber drops to room temperature, take it out and deposit a nano-Co3O4 coating with a thickness of 100 nm on the surface of the SUS430 stainless steel substrate by ALD atomic layer deposition; S3. Sintering the SUS430 stainless steel substrate with the surface ALD atomic layer deposition nano-Co3O4 coating obtained in step S2: first, heating to 600°C at a heating rate of 5°C / min in an air atmosphere, and keeping the temperature for 3 hours; then, continuing to heat to 800°C at a heating rate of 5°C / min, and keeping the temperature for 2 hours; finally, cooling to room temperature with the furnace to obtain a Co3O4 spinel structure, thereby completing the preparation of the Co3O4 nano-spinel coating (ALD-Co3O4 nano-spinel coating) on ​​the surface of the SUS430 stainless steel substrate.

[0012] The Co3O4 nano-spinel coating (ALD-Co3O4 nano-spinel coating) prepared in this example is further analyzed below in conjunction with the accompanying drawings.

[0013] 1. The ALD-Co3O4 nano-spinel coating prepared in this example was subjected to an oxidation test in air at 800°C for 200 h. The microstructure of the coating was observed using SEM every 50 h. Figure 1 As shown, the ALD-Co3O4 nano-spinel coating presents a uniform, dense and fine spinel structure after oxidation. As the oxidation time increases, the surface morphology remains stable as a whole, without cracks or peeling, indicating its good adhesion.

[0014] Second, the ALD-Co3O4 nano-spinel coating prepared in this embodiment and the samples after oxidation test were analyzed by XRD. Figure 2 As shown, except for the Fe-Cr phase of the SUS430 matrix phase, the diffraction peaks after ALD deposition belong to the Co3O4 cubic spinel phase; after isothermal oxidation, the Co3O4 diffraction peaks increase, and the CoFe2O4 spinel structure and CoMnO3 perovskite structure appear at the same time, showing a composite phase; no new phase is generated with the extension of oxidation time, and it has good thermal stability.

[0015] 3. The ALD-Co3O4 nano-spinel coating prepared in this example and the samples after thermal conversion were detected by XPS, and the peak fitting was performed using XPSPEAK41 software, as shown in FIG. Figure 3 As shown, after ALD deposition, Co 3+ / Co 2+ The ratio is 0.96, indicating that the Co3O4 film has been successfully prepared on the substrate surface after ALD deposition, and it is 1.49 after thermal conversion sintering, indicating the comprehensive formation of Co3O4 spinel.

[0016] In order to verify the high-temperature oxidation resistance, electrical conductivity and Cr resistance of the Co3O4 nano-spinel coating, the performance of the SUS430 substrate and the ALD-Co3O4 nano-spinel coating was compared, which is further explained in conjunction with the charts below.

[0017] 1. To verify the modification effect of Co3O4 nano-spinel coating on the oxidation performance of SUS430 substrate, the ALD-Co3O4 nano-spinel coating prepared in this example and the SUS430 substrate were isothermally oxidized at 800°C in air atmosphere for 50-200h, and the area ratio mass gain results of different samples after oxidation were measured. The parabolic oxidation rate constants k of the two were further calculated by the Pilling-Bedworth equation. p , as shown in Table 1.

[0018]

[0019] The oxidation kinetics curves of ALD-Co3O4 nano-spinel coating and SUS430 substrate are shown in Figure 4 As shown in the figure, the oxidation weight gain shows the characteristics of graded oxidation and is approximately in accordance with the parabolic law. After 200 h of oxidation, the mass gain of the matrix is ​​0.2 mg cm -2 The mass gain of ALD-Co3O4 nanospinel coating is even lower, only 0.12 mg cm -2 The oxidation rate constants of SUS430 substrate and ALD-Co3O4 nano-spinel coating are 6.04×10 -13 , 1.79×10 -14 g 2 cm -4 ·s -1 Compared with the substrate, the k p It is one order of magnitude lower, which indicates that the deposited Co3O4 nano-spinel coating can effectively inhibit the formation of Cr-containing oxide layer and improve the oxidation resistance of the material.

[0020] 2. In order to verify the modification effect of Co3O4 nano-spinel coating on the conductive properties of SUS430 substrate, the oxidized samples were subjected to surface resistivity tests, and the surface resistivity values ​​at different temperatures and the resistance activation energy Ea after oxidation for 150 hours were calculated. The results are shown in Table 2 below.

[0021]

[0022] Comparison of ASR curves of ALD-Co3O4 nano-spinel coating and SUS430 substrate after oxidation for 150h Figure 5 As shown in Table 2 above, ASR shows a downward trend with increasing temperature, and increases with the extension of oxidation time. The substrate has a larger ASR than the ALD-Co3O4 nano-spinel coating. Ea reflects the energy barrier that the material needs to overcome during the conduction process. The larger the Ea, the larger the barrier, the lower the conductivity of the material, and the worse the conductivity. After 150h of oxidation, the activation energies of the substrate and the ALD-Co3O4 nano-spinel coating are 0.339 eV and 0.255 eV, respectively. The activation energy and ASR of the ALD-Co3O4 nano-spinel coating are smaller, thus improving the conductivity of the material.

[0023] 3. In order to verify the improvement effect of Co3O4 nano-spinel coating on the Cr resistance of SUS430 substrate, the Cr element on the surface of the sample after oxidation test was measured by XPS, and the surface Cr element after oxidation for 200h was peak fitted using XPSPEAK41 software. The results are shown in Table 3 below.

[0024]

[0025] Comparison of relative content of Cr on the surface of ALD-Co3O4 nano-spinel coating and SUS430 substrate at different oxidation times Figure 6 As shown in the figure, the Cr content of SUS430 matrix is ​​16.21%, and after oxidation for 200h, it is 51.99%. 6+ / Cr total The value of Cr was 55.62%; no Cr was detected in the ALD-Co3O4 nano-spinel coating before oxidation, and the surface Cr content was 13.46% after oxidation for 200h. 6+ / Cr total The value is 33.28%. 6+ This will lead to an increase in the content of volatile high-valent Cr compounds, which will lead to further corrosion of the substrate. Therefore, the ALD-Co3O4 nanospinel coating can effectively prevent the diffusion of Cr in the substrate and show better high-temperature Cr resistance.

[0026] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A method for preparing a Co3O4 nano-spinel coating on a SUS430 stainless steel surface, characterized in that: The following steps are involved: S1. Substrate pretreatment: S1-1, using a wire cutting machine to cut the SUS430 stainless steel plate into substrates with a size of 15 mm in length × 15 mm in width × 1 mm in thickness; S1-2, using 120 mesh, 240 mesh, 400 mesh, 600 mesh, 800 mesh and 1000 mesh sandpaper in sequence to grind and polish the surface of the substrate prepared in step S1-1; S1-3, placing the substrate after grinding and polishing in step S1-2 into water and anhydrous ethanol in turn, performing ultrasonic cleaning for 15 to 20 minutes respectively, blowing dry after cleaning, immersing in anhydrous ethanol, sealing and storing for later use; S2, SUS430 stainless steel substrate surface ALD atomic layer deposition nano Co3O4 coating: S2-1, taking out the substrate sealed and stored in anhydrous ethanol in step S1, blowing it dry and placing it in the reaction chamber of the ALD equipment, introducing ozone into the reaction chamber with a pulse time of 30 seconds, and constructing hydroxyl active sites on the surface of the substrate; S2-2, using cobaltocene as a precursor, first, heating the cobaltocene to 80°C and then introducing it into the reaction chamber of the ALD equipment; then, setting the deposition temperature of the ALD equipment to 220°C, the precursor pulse time to 5.5 seconds, and the number of cycles to 2000 cycles; finally, standing for 16 seconds after the precursor pulse, so that the cobaltocene in the reaction chamber can fully complete chemical adsorption at the active site, and the atomic layer containing the cobalt element is deposited on the surface of the substrate by ALD atomic layer deposition; S2-3, using high-purity nitrogen as carrier gas, using high-purity nitrogen to purge, to remove unreacted precursors and by-products after the precursor pulse, the flow rate of high-purity nitrogen is 50 sccm, and the purge time is 30 seconds; S2-4. First, ozone is used as an oxidant and introduced into the reaction chamber of the ALD equipment with a flow rate of 20 sccm; then, the deposition temperature of the ALD equipment is maintained at 220° C. and the pulse time of the oxidant is 0.1 second; finally, the oxidant is allowed to stand for 25 seconds after the pulse to allow the oxidant to fully react with the cobaltocene atomic layer deposited on the surface of the substrate; S2-5, using high-purity nitrogen to purge again to remove the unreacted oxidant and by-products after the oxidant pulse, the flow rate of high-purity nitrogen is 50 sccm, and the purge time is 30 seconds; S2-6, after the temperature of the reaction chamber drops to room temperature, take it out and deposit a nano-Co3O4 coating on the surface of the SUS430 stainless steel substrate by ALD atomic layer deposition; S3. Sintering the SUS430 stainless steel substrate with the surface ALD atomic layer deposition nano-Co3O4 coating obtained in step S2: first, heating to 600°C at a heating rate of 5°C / min in an air atmosphere, and keeping the temperature for 3 hours; then, continuing to heat to 800°C at a heating rate of 5°C / min, and keeping the temperature for 2 hours; finally, cooling to room temperature with the furnace to complete the preparation of the Co3O4 nano-spinel coating on the surface of the SUS430 stainless steel substrate.

2. The method for preparing a Co3O4 nano-spinel coating on a SUS430 stainless steel surface according to claim 1, characterized in that: In the step S2-6, the thickness of the nano-Co3O4 coating deposited by ALD atomic layer deposition on the surface of the SUS430 stainless steel substrate is 100 nm.